Milne-Simpson Method for Solving First Order Fuzzy Differential Equations Using Hukuhara Approach - MOHD NOOR, MAZARINA (Enhanced Knowledge in Sciences and Technology, 2022)
This paper presents the linear multistep method used for solving fuzzy differential equations. The fuzzy differential equations will be transformed into system of ordinary differential equations using Hukuhara approach. Milne-Simpson method is used to solve the first-order fuzzy differential equations and compared the solutions with Runge-Kutta method. Numerical example is given, and numerical solution is displayed to evaluate the efficiency of the method.